Ficus racemosa L. Leaf Extracts Inhibit the Growth of the Acne Vulgaris Causing Bacterium Cutibacterium acnes - Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Acne vulgaris is a skin condition that mostly adolescents, although it also afflicts some adults. Medicinal plant extracts may provide leads for the development of new topical and/or oral therapies for acnes vulgaris, yet many traditional medicine plants are yet to be screened for growth inhibitory activity against Cutibacterium acnes (the major bacterial cause of acne). Materials and Methods: Methanolic and aqueous Ficus racemosa leaf extracts were investigated by disc diffusion and liquid dilution MIC assays against Cutibacterium acnes. Toxicity was determined using Artemia franciscana nauplii bioassays. Results: Methanolic and aqueous F. racemosa leaf extracts displayed noteworthy bacterial growth inhibitory activity against C. acnes growth. The methanolic F. racemosa leaf extract had particularly good antibacterial effects against C. acnes, with an LD MIC value of 469 μg/mL. Slightly higher LD MIC values were noted for the aqueous F. racemosa leaf extract against C. acnes (LD MIC = 875 μg/mL). The methanolic and aqueous F. racemosa leaf extracts were nontoxic in the Artemia fransiscana bioassay, with LC50 values substantially >1000 μg/mL. Conclusion: The lack of toxicity of the methanolic and aqueous F. racemosa leaf extracts and their noteworthy inhibition of C. acnes growth indicate their potential to alleviate acne vulgaris. Further studies are warranted to isolate and identify the active components and to determine their antibacterial mechanism.
Keywords: Moraceae; cluster fig; Australian medicinal plants; Acne vulgaris; Skin infection; Skin inflammation; Cutibacterium acnes; Artemia lethality assay.